Targeted Postnatal Care Implementation for Mothers in Selected Health Facilities in Western Kenya - Ruth Shitabule; Everlyne Morema; Tecla Sum; Morris Shisanya; Eric Kibai (Evidence-Based Nursing Research)
Context: Postnatal care (PNC) is essential in improving maternal health and reducing maternal mortality, especially in low-resource settings. Targeted Postnatal Care (TPNC) is an approach to postnatal care for mothers and newborns that involves a set of assessments and interventions given in four scheduled visits from birth to 6 months postpartum. The goal is to improve outcomes for these mothers and babies.